Purchasing patterns of the hotel sector in the B.V.I and the O.E.C.S. countries : final report (CEDP St MichaelBB, 1991)
Examines the hotel sector in the British Virgin Islands and the seven OECS countries. Identifies opportunities for increased consumption of local and regional products within that sector.
DC